MENGUATKAN KETAHANAN PANGAN DAERAH DENGAN MELIBATKAN MAHASISWA MEMBUDIDAYAKAN TANAMAN HORTIKULTURA DI LAHAN KAMPUS UNIVERSITAS SATYA WIYATA MANDALA NABIRE PAPUA - Wardhana Wahyu Dharsono; Hans F. Liborang; Suryadi Suryadi; Ali Waromi; Erol L. Tokoro; Aris Widodo (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2023)
Seeing the situation and experiences of the surrounding community during the pandemic, an idea emerged from the Satya Wiyata Mandala University LPPM to play an active role with students in being involved in strengthening food security in the area by cultivating horticultural crops on the campus grounds, which is a real example for the surrounding community in land management. in the vicinity of the house. Seeing the availability of sufficient land and human resources, the Satya Wiyata Mandala University LPPM made the let's plant program integrated with KKN activities that focus on cultivating vegetable crops that can meet the needs of the surrounding community. There were three stages carried out by the team before carry out activities namely the first stage of preparation, the second stage of implementation, the third carry out activity evaluation. In PKM activities, positive things were obtained, namely the activities were welcomed by the community and also became a real learning process for students who did not know about cultivating vegetable plants on land, raising awareness of students and the surrounding community to utilize the existing land around their home environment